2022
DOI: 10.3389/fmars.2022.940342
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Evolutionary Analysis of Yellow River Delta Wetlands Using Decision Tree Based on Time Series SAR Backscattering Coefficient and Coherence

Abstract: In recent years, the Yellow River Delta has been affected by invasive species Spartina alterniflora (S. alterniflora), resulting in a fragile ecological environment. It is of great significance to monitor the ground object types in the Yellow River Delta wetlands. The classification accuracy based on Synthetic Aperture Radar (SAR) backscattering coefficient is limited by the small difference between some ground objects. To solve this problem, a decision tree classification method for extracting the ground obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Using band math tool to perform mean processing on time series images. The purpose of this step is to further remove noise and reveal the mean backscattering features of different ground objects [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Using band math tool to perform mean processing on time series images. The purpose of this step is to further remove noise and reveal the mean backscattering features of different ground objects [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Confusion matrix verification (Townsend, 1971) has been proved to be effective in verifying classification accuracy. In this paper, combined with GF-2 remote sensing images with high resolution, Google Earth images and the classification results of other scholars (Wang et al, 2022;Li Z. J. et al, 2022;Zhang B. et al, 2019), 127 verification samples were used to evaluate the accuracy of classification results. The locations of verification samples are shown in Figure 8.…”
Section: Accuracy Verificationmentioning
confidence: 99%
“…With the further study, researchers found that Spartina alterniflora and other vegetation have significant differences in growth cycle. This is manifested in the differences of different spectral features (Zheng et al, 2017) and texture features (Guo et al, 2020) in optical images, and in the characteristics of backscattering coefficient (Hu et al, 2021) and coherence (Li Z. J. et al, 2022) in SAR images. At present, medium and low resolution remote sensing images are effective materials for monitoring Spartina alterniflora and vegetation classification in a large area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has limited the large-scale application and promotion of related yield estimation methods. Synthetic Aperture Radar (SAR) is not influenced by cloud, fog, rain, snow and other weather, and it can obtain image data with the advantages of day/night data acquisition, all-weather imaging capability, and strong penetrability ( Li et al., 2022 ; Wang et al., 2022 ; Yu et al., 2022 ). Satellite remote sensing can observe the earth from space over a large area.…”
Section: Introductionmentioning
confidence: 99%